Interpersonal Communication of the Save Street Child Community in Empowering Street Children in Sidoarjo Regency - Rio Agung Permana; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines how the interpersonal communication of the save street child community in empowering street children in Sidoarjo Regency. This research uses interpersonal communication theory with De Vito's educational approach. The purpose of this research is to find out how interpersonal communication between SSC community members in empowering street children in Sidoarjo Regency. The research is descriptive and the research method used is qualitative by using endid interview data collection. The results of research conducted on interpersonal communication of the save street child community in empowering street children in Sidoarjo Regency, showed that there was a positive attitude in the SSC community, being open to each other and the communication was also reciprocal. This is also in line with the communication between community members and street children and vice versa. In an effort to empower the SSC community, they first approach street children by giving milk, and the SSCS community also tries to make street children pay attention to the importance of education for street children, by establishing a program of non-formal teaching activities.